Implementation Of The Tabarak Method In Memorizing The Qur'an For Early Childhood Children - Sabitah, Anugrah; Warni, Sri; Alhamzy, M Ridwan Yusuf; Wahdana, Sukma (Nida Al-Qur'an: Jurnal Pengkajian Islam, 2024)
Early childhood children who can memorize the holy verses of the Qur'an Juz 30 in 3-4 months, this makes researchers interested in researching more deeply about how the Tabarak method is in memorizing the Qur'an. This study aims to determine the implementation of memorizing the Qur'an at the Tahfizh Center Darul Hufazh Padang City. This study uses a qualitative descriptive method. Data sources were taken from ten informants through in-depth interviews selected using purposive sampling techniques, all informants were students, foundation heads, and teachers of the Tahfizh Center Darul Hufazh Padang City. All interview results were then analyzed thematically using Nvivo 12 qualitative analysis software. Data collection techniques used were observation, interviews, and documentation. All data were analyzed using the Miles and Huberman analysis technique. The results of the study showed that there were 4 points discussed in the implementation of the Tabarak method in memorizing the Qur'an for early childhood children at the Tahfizh Center Darul Hufazh, Padang City, namely: i) Planning the Tabarak method in memorizing the Qur'an for early childhood children at the Tahfizh Center Darul Hufazh, Padang City. ii) Implementation of the Tabarak method in memorizing the Qur'an, iii) Evaluation of the Tabarak method in memorizing the Qur'an for early childhood children at the Tahfizh Center Darul Hufazh, Padang City, iv) Supporting and Inhibiting Factors of the Tabarak method in memorizing the Qur'an for early childhood children at the Tahfizh Center Darul Hufazh, Padang City. It is hoped that parents will always provide support and motivation to support the process of memorizing the Qur'an. For further researchers, this study can be used as initial data to study this problem in different contexts and issues.